Fluorine-Retentive Strategies for the Functionalization of gem-Difluoroalkenes - Sorrentino, Jacob P.; Altman, Ryan A. (Synthesis, 2021)
gem-Difluoroalkenes are readily available fluorinated building blocks, and the fluorine-induced electronic perturbations of the alkenes enable a wide array of selective functionalization reactions. However, many reactions of gem-difluoroalkenes result in a net C–F functionalization to generate monofluorovinyl products or addition of F to generate trifluoromethyl-containing products. In contrast, fluorine-retentive strategies for the functionalization of gem-difluoroalkenes remain less generally developed and is now becoming a rapidly developing area. This review will present the development of fluorine-retentive strategies including electrophilic, nucleophilic, radical, and transition metal catalytic strategies with an emphasis on key physical organic and mechanistic aspects that enable reactivities.1 Introduction2 Two-Electron Processes2.1 Elimination of Allyl Groups2.2 Electrophilic Addition2.3 Halonium and Thiiranium Intermediates2.4 Kinetic Quench of Anionic Intermediates2.5 Concerted Cycloadditions3 Radical Processes3.1 Thermal Activation3.2 Photoactivation3.3 Transition-Metal-Mediated4 Reductions5 Cross-Coupling Reactions6 Conclusions
Keywords: synthetic methodology; fluorination; gem-difluoroalkene; organofluorine